Agri-solar water pumping design, energy, and environmental analysis: A comprehensive study in tropical humid climate - Maity, Rittick; Sudhakar, Kumarasamy; Amir, Abdul Razak (Elsevier Ltd, 2024)
Agrivoltaics is an innovative approach where solar energy, water, land and biodiversity are integrated into the same area to maximize resource utilization for sustainable development, also known as Agrivoltaism. The combination of solar water pumping and agri-solar has led to the development of a new generation of irrigation systems that are highly sustainable and efficient. Agri-solar water pumping can irrigate crops, feed livestock, clean solar modules, cool the PV system, generate energy, store water, and provide community drinking water. This paper addresses the basic design and capacity requirements of solar water pumping systems for irrigating a 0.5-ha Agrivoltaics system in Kuala Lumpur. The SISIFO tool has been used to simulate the Agri-solar water pumping performance for tropical humid climatic conditions. The various parameters like site details, climate data, type of PV modules, DC pump -motor and converters are used as input data to evaluate the energy yield parameters (output energy in DC and AC form), hydraulic parameters (volume of water pumped), loss parameters (capture and system losses) and efficiency parameters (performance of the system). Lettuce was chosen as it is fast growing with good yield per hectare. Based on the result, a detailed analysis of the agrivoltaic lettuce plant is performed. A detailed analysis of the solar resource assessment, system design, Key performance indicators, loss analysis and environmental analysis of the Agri-solar water pumping has been carried out. Considering their specific climatic conditions, this can significantly assist policymakers in selecting the optimal solar pumping station for agrivoltaic plants. The importance of considering various factors when choosing a solar pumping station for agrivoltaics is also highlighted.